(untitled) (Revista Innova Educación, 2020)
This research has as a target to determine the degree of correlation between information skills and research competences in students of the IX and X cycle of the Professional School of Education of the National University Santiago Antúnez de Mayolo of the Ancash region (Peru). The approach was descriptive-correlational quantitative with census sampling, the same one that was confirmed by 88 students of both sexes. The instruments used were the research questionnaire made of Rubio (2015) and the information skills questionnaire of Cabrejos and Montenegro (2017). The results revealed, using the Spearman’s Rho non-parametric test, a moderate positive correlation of 0.3, with which it was established that there is a direct correlation between informational skills and research competences.